Association of Posterior Reversible Encephalopathy Syndrome and Transient Apical Ballooning Syndrome (Takotsubo): First Case Report of a Man and Review of the Literature - Stephan Grimaldi; Emilie Doche; Caroline Rey; Nadia Laksiri; Salah Boussen; Jacques Quilici; Emmanuelle Robinet; Fabien Devemy; Jean Pelletier (Case Reports in Neurology, 2017)
Introduction: An association of posterior reversible encephalopathy syndrome (PRES) and takotsubo is rare. We present the first case of a male patient. Case Report: A 69-year-old man presented to the hospital in a persistent comatose state following a generalized tonic-clonic seizure with high blood pressure. The electrocardiogram revealed transient left bundle branch block. Troponin and BNP were elevated. Cardiac ultrasound showed large apical akinesia with altered left ventricular ejection fraction, and the left ventriculogram showed characteristic regional wall motion abnormalities involving the mid and apical segments. Brain MRI showed bilateral, cortical, and subcortical vasogenic edema predominant in the posterior right hemisphere. The lumbar puncture and cerebral angiography were normal. Paraclinical abnormalities were reversible within 2 weeks with a clinical recovery in 3 months, confirming the takotsubo and the PRES diagnoses. Discussion: Several theories hypothesize the underlying pathophysiology of takotsubo or PRES. Circulating catecholamines are up to 3 times higher in patients with takotsubo causing impaired microcirculation and apical hypokinesia. An association of both takotsubo and asthma crisis and PRES and asthma crisis underlines the role of catecholamines in the occurrence of these disorders. Conclusion: Early recognition of this rare association, in which heart and neurological damage may require rapid intensive care support, is needed.